2009
DOI: 10.2174/1874418400903010001
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Native Cytomegalovirus Pancreatitis Following Deceased-Donor Renal Transplantation

Abstract: Cytomegalovirus (CMV) is a known cause of pancreatitis in immunocompromised patients, usually in association with the human immunodeficiency virus [1]. A handful of cases have been reported of CMV pancreatitis occurring in a transplanted pancreas secondary to immunosuppression associated with organ transplantation. Herein, we report a rare case of CMV pancreatitis following deceased-donor renal transplantation in which a patient's native pancreas was infected by CMV transmitted by donor renal tissue. After ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…An autopsy study found that approximately 10% of patients with CMV infection have pancreas involvement, although selection bias of severe disease is expected [ 35 ]. Most diagnoses in case reports are based on acute pancreatitis in the setting of CMV viremia with demonstrated response to CMV treatment [ 36 – 38 ]. Cholangitis with CMV involvement of the biliary epithelium has also been reported [ 39 ].…”
Section: CMV In the General Population: Presentation Diagnosis Amentioning
confidence: 99%
“…An autopsy study found that approximately 10% of patients with CMV infection have pancreas involvement, although selection bias of severe disease is expected [ 35 ]. Most diagnoses in case reports are based on acute pancreatitis in the setting of CMV viremia with demonstrated response to CMV treatment [ 36 – 38 ]. Cholangitis with CMV involvement of the biliary epithelium has also been reported [ 39 ].…”
Section: CMV In the General Population: Presentation Diagnosis Amentioning
confidence: 99%
“…A study using a pathologic examination revealed ulcerations and necrosis with scattered CMV inclusions (28). Duodenal vasculitis, intermittent small-bowel obstruction, acute pancreatitis, bloody ascites, colonic obstruction, and painful hemorrhoids have been reported as rare gastrointestinal presentations of CMV infection (28-36). Rare gastrointestinal presentations of CMV infection in kidney-transplant recipients are shown in Table 2.…”
Section: Gastrointestinal Complicationsmentioning
confidence: 99%